RASM AL-USMANI DI KALANGAN SANTRI (STUDI RESEPSI AL-QUR'AN DI PONDOK PESANTREN AL-HIDAYAH KARANGSUCI PURWOKERTO) - Akhmad Roja Badrus Zaman (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
In the book Manahil al-Irfan fi Ulumil Qur’an, it is stated that what is meant by Rasm al-usmani or al-Mushaf is the principle agreed upon by Uthman (r) in the writing of Al-Qur’an sentences and letters. Some countries like Pakistan, Lebanon and Indonesia have different standards in the writing of the Qur’an, which includes punctuation, completeness of recitation, and other punctuation devices, such as sifir, isymam, imalah, tashil, and so on. Since 1984 through the Minister of Religion (KMA) number 25, Indonesia has three types of standard Al-Qur’an manuscripts, namely Ottoman Standard Mushaf, Bahriyah Mushaf, and Braille Manuscripts. Manuscripts of the Ottoman Standard are used as references for the publication and circulation of the Qur’an in Indonesia. In reality, not all people use the standard Ottoman Manuscripts, such as the Al-Hidayah Islamic Boarding School in Karangsuci Purwokerto applying the rules of obligation to use mushaf Rasm al-usmani published by the Middle East with the perception that the Middle East’s Manuscripts are the most Ottoman manuscripts. This, according to the author, tends to blur and simplify the diversity of writing on Rasm al-usmani. This paper tries to elaborate on the subject as well as matters relating to it. From the research conducted it can be seen that the Mushaf is just a device. There is no problem the community wants to use the Mushaf, because in fact the Al-Qur’an recitation is very much based on the aspects of talaqqi, the continuation of the sanad and the path of transmission, not solely dependent on khat, rasm, or writing.